Micro uncertainty and the lending channel: Bank-level evidence in an emerging market - Thuy Tien Ho (Global Business & Finance Review (GBFR), 2024)
Purpose: Existing research on uncertainty and bank lending has focused entirely on aggregate uncertainty (i.e., economic policy uncertainty) and its subcomponents, but not considering other uncertainty measures from the specif-ic perspective of financial markets, especially the banking sector. The paper tests the influence of uncertainty on loan growth using bank-level data in Vietnam during 2007-2019. Design/methodology/approach: The paper focuses on a new uncertainty measure in banking computed by the dispersion of shocks to key bank-level variables. The study also fixes the issues of potential endogeneity bias by using dynamic panel models with the generalized method of moments (GMM) estimator. Findings: Uncertainty in banking hampers loan growth. The adverse influence of uncertainty on lending is more pronounced for banks that are smaller, more poorly capitalized, less liquid, riskier, and less profitable. In addition, the paper also provides evidence that bank lending under uncertainty is not moderated by bank ownership, i.e., the paper does not find a discrepancy in the banking uncertainty-bank lending nexus between state-owned banks and private counterparts. Research limitations/implications: Regulatory bodies should enhance their scrutiny concerning uncertainties within the banking sector, recognizing their potential to adversely affect bank lending, a critical catalyst for fostering economic activity. Simultaneously, it is imperative to implement concurrent policies aimed at mitigating the delete-rious consequences of uncertainty in bank lending. Originality/value: First, this paper is interested in an emerging market, given that the evidence from emerging markets has remained remarkably scarce. Second, this paper approaches the banking sector's uncertainty and as-sesses its link with bank lending. Third, this study contributes to the literature by investigating the nuanced con-ditions influencing the impact of uncertainty through an extensive array of moderating factors. Interestingly, this paper is the first to examine the conditional role of state ownership thus far.
Keywords: 650; bank lending; bank-level shocks; emerging market; state ownership; uncertainty